The Socio-demographics and Clinical Characteristics and CD4 Profile of HIV/AIDS Patients Receiving First Line Antiretroviral Therapy at a Public Hospital in Palu - Alwiyah Mukaddas; Ingrid Faustine; Pupuy Astarina Pilanto; Nurhayati Adnan (Future Science, 2023)
The Joint United Nations Program on HIV/AIDS (UNAIDS) set the pushful 90-90-90 target in 2015. It can be a difficult target to achieve without a comprehensive understanding of HIV epidemiology. This study aims to identify demographic and clinical characteristics and determine the difference between CD4 counts pre and post-antiretroviral (ARV) therapy in HIV patients of HIV/AIDS at a Public Hospital in Palu. A retrospective cross-sectional study of 27 HIV/AIDS patients was conducted between January 2011 and December 2015. Data were collected from medical records and electronic registries for HIV/AIDS patients. The study included 27 patients with complete data set from 230 patients, 63% productive age (25 - 44 years), 77,8% male, 85,2% were employed, 48,1% were well educated (from senior high school and equal), and 59,3% were married. The majority of patients acquired HIV through heterosexual transmission, 40,7%. At the time of the first clinic visit, 40,7% of patients had WHO stage III HIV infection. The rates of Candidiasis and TB coinfections were 22,2% and 18,5%, respectively. ZDV/3TC/NVP (74,1%) is the most commonly used antiretroviral combination. The baseline CD4+ cells count was < 350 cells/mm3 in 100% (n = 27) of patients, CD4+ median 126 cells/mm3. After Antiretroviral Therapy (ART) 6 months, two patients had a normal range CD4 500-1300 cells/mm3, CD4+ median 203 cells/mm3. There was a significant increase in CD4 count after ARV therapy (p=0,000; p<0,05). It suggests that ARV therapy can improve CD4 and immune recovery in HIV/AIDS patients.